An Industrial Dental-Erosion by Chromic Acid: A Case Report - Dülgergil, Ç. Türksel (Dental Investigations Society, 2007)
A case of uncommon occupational dental erosion was reported in an individual who had worked in the war industry for twenty years. This occupation involved daily, at least 8 hours, inhalation of chromic acid being used for cleaning of barrel of cannons. The erosion manifested as dental sensitivity with excessive cervical erosion even with pulpal exposure in certain teeth. Moreover, due to the adverse effect of the chemical against to gingival and/or periodontal tissues, the lesions were extremely harmful with respect to the exposed root-cementum. After proper periodontal therapy, cervical lesions were treated conservatively with a compomer based restorative material without cavity preparation. Although today it is not common due to the well-controlled working conditions, occupational combined dental and medical problems via airborne fumes and/or elements can be seen at workers in chemical factories. A cumulative biohazardous effect is generally seen as not only medical but also dental disorders.